The Radioactive Sands & Low-Resistivity Low-Contrast Pays Reservoir in Deta Field, Niger Termit Basin - Chang, Eevon; Zung Lo, Shyh (International Journal of Engineering and Technology, 2018)
Radioactive and low-resistivity pay sands are often petrophysically underestimated under conventional exploration approaches. Deta Field is a good example of hydrocarbon producing field with low resistivity contrast and radioactive sands. Deta field located in the South-West flank of Dinga Trough, Termit Basin. Hydrocarbon had been discovered and produced from Alter Sokor formation, E0-E5 sand zones. Radioactive sands found in Deta field reservoir formations are due to clay minerals in sandstone composition. Types of clay minerals in radioactive sands are studied from E0 and E1 formations after the crossplot analysis using Spectral Gamma Ray (SGR) log, photoelectric log, and density-neutron log crossplot. High percentage of illite are found as types of clay minerals in radioactive sand. The low resistivity pays identified in the main hydrocarbon producing reservoir sand zones are due to the dispersed clay minerals. The oil-producing reservoir sandstone recorded with relatively low resistivity curve of 15 - 20 ohm∙m only. The difference of resistivity curve between reservoir intervals and adjacent shale formation is less than 7 ohm∙m. This study aims to understand the clay content in radioactive sands and relate to low resistivity pays reservoir. This research finds that both reservoir problems of radioactive sands & low resistivity pays are indirectly related.